Formaldehyde-free veneer and preparation method thereof
Through the anti-aldehyde-free adhesive and polymer surface treatment technology, combined with the low-temperature bonding process, the problem that impregnated adhesive film paper decorative panels cannot achieve insufficient wear resistance on the surface of the anti-aldehyde-free and prepreg paper paper decorative panels are realized. The environmentally friendly, durable and diverse decorative effects reduce production energy consumption.
Patent Information
- Application Number
- CN202411554823.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing artificial boards with impregnated adhesive film paper are unable to achieve true aldehyde-free addition, and the surface of the prepregated paper paper panel is not wear-resistant and scratch-resistant, which affects its service life and decorative effect.
Using the aldehyde-free adhesive technology, polymer surface treatment technology and low-temperature bonding and low-energy production technology, the artificial paper-free paper finishing artificial board is prepared, and the artificial-free plywood and fine wooden board are used as substrates, combined with improved pre-impregnation The paper is composited using a flat sticking process to ensure the entire veneer's aldehyde-free characteristics and high surface performance.
The environmental protection performance of the aldehyde-free veneer panel is achieved, the formaldehyde release is avoided, the surface hardness and wear resistance are improved, the service life is extended, the needs of different decoration styles are met, and the production energy consumption is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of formaldehyde-free artificial board manufacturing, and in particular to a formaldehyde-free decorative panel and a preparation method thereof. Background Art
[0002] Impregnated film paper facing wood-based panels are the most widely used indoor decoration materials in the field of home decoration, and their environmental performance has attracted much attention from consumers. The environmental performance of conventional impregnated film paper facing wood-based panels on the market can generally reach E0 level or even ENF level, but their formaldehyde emission is only the value measured under normal temperature of 23℃ and humidity of 50%. As the temperature rises, the formaldehyde emission of products using urea-formaldehyde adhesive system increases exponentially, resulting in a 3-10-fold increase in formaldehyde emission of the panels in summer or when heating is used in the north, which reduces the indoor air quality and affects people's health.
[0003] Impregnated film paper veneer wood-based panels are made of wood-based panels as the base material and impregnated film paper as the veneer material, which are pressed under high temperature and high pressure. Although the current adhesive level is developing rapidly, trialdehyde glue, lignin glue with low formaldehyde content, and even soybean glue without formaldehyde addition have been developed and used in product manufacturing, trialdehyde glue and lignin glue contain formaldehyde themselves, and soybean glue cannot be used in the entire production process of impregnated film paper veneer wood-based panels due to poor coarse viscosity and fast drying of glue, resulting in the inability of solid wood veneer wood-based panels to be truly formaldehyde-free. Especially for veneer panels with impregnated paper as the veneer material, because impregnated paper currently generally uses trialdehyde glue as the impregnation material, it cannot even reach the threshold of formaldehyde-free panels.
[0004] Europe, America, Japan and other places have successively introduced ultra-low formaldehyde decorative panels made of Polaroid paper, gorgeous paper, pre-painted paper and other finishing materials instead of impregnated film paper. However, due to the low surface hardness of these finishing materials, the decorative panels prepared with them have defects such as scratch resistance and wear resistance. Scratches are easily caused during the subsequent processing of furniture panels, affecting the appearance and service life. Therefore, they have not been widely used as decorative materials for interior decoration.
[0005] Some European home furnishing brands pay great attention to the environmental protection of furniture and energy saving in the production process. They use ultra-low formaldehyde artificial boards as the base material and pre-painted paper as the finishing material to prepare "formaldehyde-free veneer artificial boards". However, their base material is limited to particle boards and cannot be realized on plywood and blockboards. At the same time, their products have extremely poor surface wear resistance, scratch resistance, hardness and other properties, and the color and texture are single. Generally, they can only be made into flat products, which are not accepted by consumers in the domestic market. At the same time, due to its poor surface performance, scratches often appear in the subsequent processing process, resulting in a high rate of board failure, and it cannot be widely promoted in many furniture processing factories. Summary of the invention
[0006] The object of the present invention is to provide a formaldehyde-free decorative panel and a preparation method thereof, so as to solve the problems that the existing impregnated paper decorative panels cannot be formaldehyde-free and the surfaces of the pre-impregnated paper decorative panels are not wear-resistant and scratch-resistant.
[0007] The present invention integrates formaldehyde-free adhesive technology, polymer surface treatment technology and low-temperature bonding and low-energy production technology of artificial boards to prepare a paper-faced artificial board with no formaldehyde, high surface performance and low carbon emissions, and provides a facing artificial board that is truly formaldehyde-free and suitable for customized production lines and its preparation method, using formaldehyde-free board core, core board, and balance layer as raw materials, and using formaldehyde-free adhesive water-based polyurethane adhesive as a special adhesive to prepare formaldehyde-free plywood and formaldehyde-free blockboard. A formaldehyde-free decorative panel preparation process provided by the present invention uses formaldehyde-free blockboard and plywood as substrates, pre-impregnated paper decorative materials on the surface, and uses polyurethane adhesive flat pasting technology to complete the composite of the substrate and the decorative layer to prepare formaldehyde-free paper-faced artificial boards. At the same time, it uses low-temperature and low-pressure processes in the production process to reduce energy consumption and has a large energy-saving effect.
[0008] The present invention provides a formaldehyde-free decorative panel, which specifically comprises: a formaldehyde-free substrate and formaldehyde-free decorative paper; The formaldehyde-free substrate includes formaldehyde-free plywood and formaldehyde-free blockboard; The formaldehyde-free facing paper is improved pre-impregnated paper; The formaldehyde-free decorative panel is produced by compounding a formaldehyde-free base plate and a formaldehyde-free decorative paper using a flat-pasting process.
[0009] Formaldehyde-free substrates avoid the release of formaldehyde during use, providing a healthier guarantee for the indoor environment. The improved pre-impregnated paper also does not contain formaldehyde. When combined with the formaldehyde-free substrate, the source of formaldehyde is eliminated from the two main parts of the veneer. This makes the entire veneer meet strict environmental standards, helps reduce indoor air pollution, and is a green and environmentally friendly decorative material. Formaldehyde-free facing paper is an improved pre-impregnated paper that can provide a variety of decorative effects, simulate various wood textures, stone textures, etc., and can meet the needs of different decoration styles. Formaldehyde-free plywood and formaldehyde-free blockboard as substrates have good strength and stability. Plywood is made of multiple layers of thin boards glued together, and the internal structure of the blockboard is stable. They can provide a solid foundation for the veneer, giving it good anti-deformation ability. When subjected to certain external forces, such as daily collisions and extrusions, it is not easy to be damaged, ensuring the quality and durability of the veneer.
[0010] The flat lamination process can make the formaldehyde-free substrate and the formaldehyde-free facing paper tightly laminated. This process can ensure a high degree of adhesion between the facing paper and the substrate, and reduce quality problems such as hollowing and bubbling. During long-term use, the surface flatness of the veneer can be well maintained, and there will be no deformation or peeling of the facing paper due to loose adhesion, thereby improving the service life and aesthetics of the veneer.
[0011] Preferably, the formaldehyde-free substrate specifically comprises: a base material layer, a balancing layer and a hardened base coating layer; The substrate layer is one or two formaldehyde-free core wood panels and eucalyptus core panels, which are prepared by using formaldehyde-free adhesives through gluing, assembly, cold pressing, core trimming, hot pressing, thickness sanding, trimming, and polishing processes; the moisture content of the core wood panel is 5-8%, and the moisture content of the eucalyptus core panel is 6-12%. The balancing layer is a bleached poplar veneer or a high-density fiberboard without added formaldehyde; The hardened base coating has a smoothness of Ra0.3-0.5 after sanding, and a surface hardness of 3-5H.
[0012] The use of formaldehyde-free adhesives to prepare the substrate layer further ensures the formaldehyde-free characteristics of the entire substrate. In indoor environments, the release of formaldehyde mainly comes from chemical substances such as adhesives. The use of formaldehyde-free adhesives avoids this potential source of pollution, ensures indoor air quality, and is very beneficial to the health of residents.
[0013] It is prepared through multiple processes such as gluing, assembly, cold pressing, core trimming, hot pressing, thickness sanding, trimming, polishing, etc. These complex process steps ensure the quality of the substrate layer. The hot pressing process can make the internal structure of the board more compact and improve its strength and stability; the thickness sanding and polishing process can make the surface of the board more flat and smooth, providing a good foundation for the subsequent adhesion of the balancing layer and hard base coating.
[0014] The moisture content of the core of the blockboard and the eucalyptus core board is strictly controlled. The moisture content of the core of the blockboard is 5-8%, and the moisture content of the eucalyptus core board is 6-12%. The appropriate moisture content can prevent the board from deforming, cracking and other problems due to moisture changes during use. Under different environmental humidity conditions, this moisture content control can keep the board stable and extend its service life.
[0015] The balancing layer uses formaldehyde-free poplar bleached veneer or high-density fiberboard, which echoes the formaldehyde-free concept of the base material layer. The entire base material implements environmental protection requirements from the inside to the outside. Formaldehyde-free materials avoid pollution to the indoor environment due to the release of chemical substances, and the environmental protection characteristics are more advantageous.
[0016] Poplar bleached veneer has good decorative properties, and its lighter color can provide a relatively uniform base color for the veneer, which is convenient for subsequent processing and decoration. At the same time, high-density fiberboard has higher density and strength, which can enhance the overall structural performance of the substrate, making the substrate more durable and more resistant to deformation and external damage.
[0017] The surface hardness of the hardened base coating reaches 3-5H, and this higher hardness enables the veneer to resist scratches and wear in daily use. The finish after sanding is Ra0.3-0.5, which means that the surface of the base coating is very smooth, which not only improves the appearance quality of the veneer and makes it look more refined, but also makes it easier to clean. The smooth surface is not easy to be stained with dust and stains, and even if there are stains, it is easier to wipe clean, reducing the difficulty and frequency of cleaning.
[0018] The present invention provides a method for preparing a formaldehyde-free decorative panel, and the specific process flow includes: S1 Formaldehyde-free adhesive preparation; S2 Formaldehyde-free plywood and formaldehyde-free blockboard substrate preparation; S3 formaldehyde-free plywood and formaldehyde-free blockboard substrate production; S4 formaldehyde-free substrate hardened; S5 high surface performance formaldehyde-free paper preparation; S6 formaldehyde-free decorative panel composite production.
[0019] The preparation of formaldehyde-free adhesives is the key starting point for the production of formaldehyde-free decorative panels. Traditional adhesives are often the main source of formaldehyde release, but by specially preparing formaldehyde-free adhesives, formaldehyde is eliminated from the source in the production of decorative panels, which is crucial for the production of environmentally friendly decorative panels. This adhesive can ensure that in the subsequent substrate preparation and the entire decorative panel production process, formaldehyde pollution will not be generated due to the adhesive, so that the final product meets strict environmental protection standards and is conducive to improving indoor air quality.
[0020] The preparation of formaldehyde-free plywood and formaldehyde-free blockboard substrates is an important step in ensuring the quality of decorative panels. Through this step, key factors such as the wood quality, fiber direction, and board density of the substrate can be controlled. In the preparation of plywood substrates, selecting high-quality wood and reasonably arranging the synthesis of veneers can make plywood have good mechanical properties; for blockboards, the splicing and arrangement of core materials can be optimized to improve their flatness and stability. The formaldehyde-free preparation process in the preparation of formaldehyde-free plywood and formaldehyde-free blockboard substrates ensures that the substrate itself does not contain formaldehyde, which is completely consistent with the formaldehyde-free positioning of decorative panels. This consistency makes the entire decorative panel more reliable in environmental performance and avoids harm to the indoor environment due to formaldehyde release from the substrate. Moreover, during the subsequent processing and use, the formaldehyde-free substrate will not react chemically with other formaldehyde-free materials to release formaldehyde, ensuring the long-term environmental protection of the decorative panel.
[0021] In the process of making formaldehyde-free plywood and formaldehyde-free blockboard substrates, formaldehyde-free plywood and formaldehyde-free blockboard are reasonably combined and processed to form a substrate with good structural integrity. Through a specific pressing process, plywood and blockboard can be closely combined to make up for the possible structural defects of each. The multi-layer structure of plywood and the core-veneer structure of blockboard cooperate with each other to enhance the deformation resistance of the substrate, so that it can maintain good flatness and stability under different environmental conditions of temperature and humidity changes, providing a solid foundation for the long-term use of decorative panels.
[0022] The surface hardness of the formaldehyde-free substrate after hardening treatment is significantly improved. After hardening treatment, the substrate can better resist friction and collision forces, reduce surface scratches and wear, and maintain the beauty and service life of the decorative panel. Hardening treatment can not only increase the hardness, but also improve the stability of the substrate surface. It can make the surface flatter and smoother, and reduce surface deformation caused by external factors during long-term use. This stable surface provides better conditions for the subsequent facing paper lamination, which can make the facing paper and the substrate fit more closely and evenly, avoiding quality problems such as blistering and degumming.
[0023] The preparation of formaldehyde-free paper with high surface performance, on the one hand, continues the environmental protection concept of formaldehyde-free, ensuring that the decorative panels will not introduce formaldehyde in the finishing process. On the other hand, this paper has excellent decorative properties, and can simulate the texture and color of various natural materials through printing, impregnation and other processes to meet the personalized decoration needs of different consumers. Formaldehyde-free paper with high surface performance also has advantages in strength and stain resistance. It has a certain tear resistance and is not easily damaged during processing and installation. At the same time, it can be specially treated to improve stain resistance, making the decorative panels easier to clean and maintain in daily use.
[0024] During the composite production of formaldehyde-free veneer panels, the formaldehyde-free substrate and high-surface-performance formaldehyde-free paper are combined through the composite production of the flat-pasting process, giving full play to the advantages of both. The strength and stability of the substrate are integrated with the decorativeness and environmental protection of the facing paper to form a decorative panel that is both beautiful and practical. This composite structure enables the veneer panels to be used in a variety of environments, whether as wall decoration or furniture surface decoration. The composite production process can achieve large-scale and efficient production. Through the flat-pasting process, the facing paper and the substrate can be quickly and accurately bonded together, ensuring product quality while improving production efficiency. This helps to reduce production costs, making formaldehyde-free veneer panels more competitive in the market, and can be more widely promoted and applied to meet the growing market demand for environmentally friendly decorative materials.
[0025] Preferably, the formaldehyde-free adhesive is a modified acrylic resin adhesive, and the preparation of the formaldehyde-free adhesive is the preparation of the modified acrylic resin, and the specific steps include: S11 prepare raw materials: 20-25 parts of acrylic acid monomer, 50-60 parts of acrylate monomer, 10-16 parts of hydroxyl functional body, 5-10 parts of polyvinyl alcohol, 2-4 parts of emulsifier, 0.02-0.06 parts of initiator, 60-90 parts of deionized water; The acrylic acid monomer is one or a mixture of two of acrylic acid, methyl acrylate or ethyl acrylate; The acrylic acid ester monomer is obtained by methyl acrylate and isoprene glycol through an ester exchange reaction; Preparation of S12 modified acrylic resin emulsion: First, acrylic acid monomer, acrylic ester monomer and deionized water are mixed, and then hydroxyl functional body, polyvinyl alcohol, emulsifier and initiator are added, and the mixture is reacted for 2-6 hours at 40-80° C. and 300-800 rpm under nitrogen protection to obtain a modified acrylic resin emulsion; Preparation of S13 modified acrylic resin glue: The prepared modified acrylic resin emulsion is taken as the main body, a part of flour is added as filler, and a certain amount of humidity regulating materials such as calcium chloride or magnesium chloride is added, and the mixture is stirred at a high speed of 500-3000 revolutions per minute for 10-15 minutes to prepare modified acrylic resin glue; the modified acrylic resin emulsion: flour: humidity regulating material = 80-100:20-25:0.5-1.
[0026] The formaldehyde-free adhesive prepared by this process has high performance and is extremely innovative. The modified acrylic resin emulsion is the main body. The acrylic resin emulsion itself has good bonding performance and flexibility. It can form a uniform adhesive film on the surface of different materials and can adapt well to the surface microstructure of materials such as wood, thereby providing a better bonding effect; the selection of acrylic monomers and acrylate monomers is targeted. Acrylic monomers such as acrylic acid, methyl acrylate or ethyl acrylate, as well as acrylate monomers obtained by ester exchange reactions, can provide a good polymerization basis to form polymers with suitable molecular weight and molecular structure, thereby giving the adhesive good bonding performance and flexibility; the addition of hydroxyl functional bodies can participate in subsequent cross-linking reactions, etc., to increase the cohesion and bonding strength of the adhesive; the addition of polyvinyl alcohol can play a role in thickening and stabilizing the emulsion, making the adhesive more stable during storage and use; the ratio between the raw materials is optimized to ensure the formation of a modified acrylic resin emulsion with excellent performance during the reaction process.
[0027] Adding a portion of flour as filler can increase the volume of the adhesive and reduce costs. At the same time, it can also improve the rheological properties of the adhesive to a certain extent, making it easier to operate during the gluing process and making the viscosity of the adhesive more moderate, neither too thin to cause flow nor too thick to be difficult to apply.
[0028] With the help of a certain amount of humidity regulating materials, the humidity of the environment around the adhesive can be adjusted, which helps the adhesive maintain an appropriate moisture content during the curing process and avoids the bonding effect being affected by excessive moisture loss or excessive absorption. In a dry environment, humidity regulating materials can prevent the adhesive from drying out too quickly and cracking. In a humid environment, they can prevent the adhesive from absorbing too much moisture and becoming soft and having reduced viscosity.
[0029] The reaction is carried out under nitrogen protection to avoid the interference of oxygen on the polymerization reaction, reduce the occurrence of side reactions, and is conducive to the formation of high-quality modified acrylic resin emulsion. The reaction temperature is 40-80℃, the stirring speed is 300-800 rpm, and the reaction lasts for 2-6 hours. The appropriate temperature and stirring speed can ensure that the monomers are fully polymerized to form polymers with a reasonable molecular weight distribution; too high a temperature may cause the polymerization reaction to be too fast, resulting in polymers with too large or too small molecular weight, affecting the performance of the adhesive; too low a temperature will cause the reaction to be too slow and inefficient. The appropriate stirring speed can fully mix the reactants and promote uniform reaction; high-speed stirring can fully mix the components to ensure good synergy between the modified acrylic resin emulsion, flour and humidifying materials. Uniform mixing can avoid problems such as inconsistent bonding strength caused by uneven local components, so that the adhesive has stable performance throughout the entire use process.
[0030] Due to its reasonable formula design and sufficient mixing process, the formaldehyde-free adhesive prepared by the present invention has advantages in bonding performance; compared with the formaldehyde-free adhesives available on the market, it is formaldehyde-free and environmentally friendly, can better adapt to the surface characteristics of substrates and finishing materials, provide more uniform bonding strength, reduce costs and improve economic value.
[0031] Preferably, the preparation of the formaldehyde-free plywood and formaldehyde-free blockboard substrate comprises the following specific steps: S21 prepare materials: formaldehyde-free adhesive and core material; The formaldehyde-free adhesive is a modified acrylic resin adhesive; The core material is one or two kinds of formaldehyde-free blockboard core and eucalyptus core board; the moisture content of the blockboard core is 5-8%, and the moisture content of the eucalyptus core board is 6-12%; S22 Gluing and Assembly: The core materials are assembled in a crisscross pattern according to the design plan. The amount of formaldehyde-free adhesive applied is 160-170g / m², and the gluing time is controlled within 40-60 minutes. S23 cold pressing: set the cold pressing time to 40-80 minutes and the pressure to 0.6-0.9MPa; S24 core repair: cut off the overlap and fill the gap between the missing core and the gap; S25 hot pressing: temperature 120-130℃, time 20-60 minutes, pressure 0.6-0.9MPa, hot pressing to the moisture content of the blank is 7-9%, moisture content deviation is 1-2%; after cold pressing, the blank is hot pressed within 12 hours; S26 fixed thickness sanding: select 60 and 120 mesh combination sanding belts, sand to the specified thickness of 15-16mm, the thickness deviation of the board is within 0.2mm, and the board surface finish is Ra1.5-1.7; S27 scraping putty: fill the missing core of the flat surface; S28 trimming: One-time trimming to obtain formaldehyde-free plywood and formaldehyde-free blockboard substrates, with a cutting amount of 20-30mm; S29 curing: the curing period is 5-8 days, and the formaldehyde-free plywood and formaldehyde-free blockboard substrate are obtained.
[0032] The present invention improves the gluing quality of the board by reasonably controlling the parameters such as the glue coating amount, the gluing time, the cold pressing time and the pressure in the preparation process of the formaldehyde-free plywood and the formaldehyde-free blockboard substrate, makes the gluing between the board core materials more firm, and reduces the occurrence of quality problems such as delamination and cracking; ensures that the performance of the board is more stable during subsequent processing and use, and in subsequent processes such as hot pressing, sanding, and trimming, the board is not easily deformed or damaged due to the good gluing quality.
[0033] The glue application amount and time of this process are determined according to the characteristics of the formaldehyde-free adhesive (modified acrylic resin glue) used and the properties of the core material (formaldehyde-free joinery core, eucalyptus core board). The glue application amount is 160-170g / m², and the glue application time is controlled at 40-60 minutes; the appropriate glue application amount and time can ensure that the adhesive is fully distributed on the surface of the core material and can form a good bonding effect in the subsequent cold pressing process; too much glue application will cause the adhesive to overflow and affect the appearance and quality of the board; too little glue application will result in loose bonding; too long glue application time will cause the adhesive to partially dry during the glue application process, affecting the bonding effect; too short glue application time will prevent the adhesive from being evenly distributed. This process sets the cold pressing time to 40-80 minutes and the pressure to 0.6-0.9MPa; the parameters of the cold pressing time and pressure are determined based on the moisture content of the core material (the moisture content of the core of the blockboard is 5-8%, and the moisture content of the eucalyptus core board is 6-12%) and the curing characteristics of the adhesive; appropriate cold pressing time and pressure can allow the core materials to fully contact during the gluing process, exclude air, and allow the adhesive to cure under appropriate pressure and time conditions to form a strong gluing connection; if the cold pressing time is too short or the pressure is too small, the gluing will not be strong; if the cold pressing time is too long or the pressure is too high, the core material will be damaged and the performance of the board will be affected.
[0034] The cold pressing parameters of this process match the characteristics of the formaldehyde-free adhesive (modified acrylic resin glue). Appropriate time and pressure conditions during the cold pressing process can fully cure the adhesive and give full play to its bonding performance. Under a pressure of 0.6-0.9MPa and a cold pressing time of 40-80 minutes, the modified acrylic resin glue can better fill the pores of the core material and form a strong bonding connection. This coordinated synergistic effect can improve the overall quality of the board. Because the adhesive can give full play to its performance, the performance indicators of the board such as bonding strength and flatness are improved, making the final produced formaldehyde-free plywood and formaldehyde-free blockboard substrates of better quality.
[0035] Preferably, the formaldehyde-free plywood and formaldehyde-free blockboard substrate are produced by the following specific steps: S31 Prepare materials: formaldehyde-free adhesive; formaldehyde-free plywood and formaldehyde-free blockboard substrate; poplar bleached veneer or high-density fiberboard balance layer; The formaldehyde-free adhesive is a modified acrylic resin adhesive; The water content of the poplar bleached veneer is 8-12%, and the density of the high-density fiberboard is 800-950kg / m³; S32 Glue coating: A bleached poplar veneer or high-density fiberboard balancing layer is laminated on the top and bottom of the formaldehyde-free plywood and formaldehyde-free blockboard substrates, and the amount of formaldehyde-free adhesive coating is 140-150g / m 2 , the gluing time is controlled within 20-40 minutes; S33 cold pressing: within 40-70 minutes, pressure 0.7-0.75MPa; S34 hot pressing: set the hot pressing temperature to 115-125℃, the time to 5-10 minutes, the pressure to 0.6-0.9MPa, and control the moisture content after hot pressing to 7-8%; S35 sanding: Use 240-250 mesh sanding belt to polish, sand until the thickness deviation of the board is within 0.15mm, the board surface is flat, and the finish is Ra0.7-0.9; S36 trimming: Second trimming to obtain formaldehyde-free plywood and formaldehyde-free blockboard substrate; S37 curing: setting the number of days to 8-12 days, to obtain the formaldehyde-free plywood and formaldehyde-free blockboard substrate.
[0036] Modified acrylic resin glue is selected as the formaldehyde-free adhesive, which has good bonding properties. It can effectively bond the plywood and blockboard substrates with the balancing layer without formaldehyde. Compared with traditional formaldehyde-containing adhesives, it avoids the risk of formaldehyde release while ensuring the bonding strength, ensuring the environmental friendliness of the decorative panels. In addition, acrylic resin glue itself has good water resistance and weather resistance, so that the decorative panels can still maintain good structural stability in humid environments or when the temperature changes greatly.
[0037] For poplar bleached veneer, controlling its moisture content at 8-12% is a key factor. The appropriate moisture content can ensure that the veneer will not crack due to excessive drying during subsequent processing, nor will it deform due to excessive moisture content. After being compounded with the substrate, it can better adapt to changes in environmental humidity and reduce board deformation caused by moisture changes.
[0038] The density of high-density fiberboard is 800-950kg / m³. Fiberboard in this density range has high strength and stability. It can provide good support for the baseboard, enhance the overall structural performance of the baseboard, make the baseboard less likely to deform when subjected to external forces, and can work better with other materials to ensure the flatness and durability of the veneer.
[0039] The amount of formaldehyde-free adhesive applied is 140-150g / m². This amount of adhesive can ensure that enough adhesive covers the substrate and the balancing layer to ensure a good bonding effect. The application time is controlled within 20-30 minutes. This time range allows the adhesive to fully penetrate into the wood fiber and make the bond stronger. Appropriate application amount and time control can effectively prevent the balancing layer and the substrate from delaminating during subsequent processing and use, thereby improving the quality and stability of the substrate.
[0040] A bleached poplar veneer or high-density fiberboard balancing layer is laminated on the top and bottom of the formaldehyde-free plywood and formaldehyde-free blockboard substrates. This symmetrical composite structure can make the stress distribution of the substrate in the thickness direction more uniform. When the veneer is subjected to external environmental factors such as humidity changes, temperature changes, or external forces, it can better resist deformation and maintain overall flatness, thereby extending the service life of the veneer.
[0041] Apply 0.7-0.75MPa pressure for cold pressing within 40-70 minutes. This cold pressing process can initially solidify the adhesive at a lower temperature, making the bond between the substrate and the balance layer tighter. Appropriate pressure and time can ensure the bonding effect while avoiding damage to the wood structure due to excessive pressure or too long time, maintaining the original properties of the wood, and providing a good foundation for the subsequent hot pressing process.
[0042] The hot pressing temperature is set at 115-125℃, the time is 5-10 minutes, and the pressure is 0.6-0.9MPa. This combination of hot pressing parameters can fully cure the adhesive and further enhance the bonding strength between the substrate and the balance layer. Within this temperature and pressure range, the moisture in the wood will also be properly adjusted. The moisture content after hot pressing is controlled at 7-8%, so that the substrate reaches an ideal moisture balance state, which helps to improve the stability and dimensional accuracy of the substrate and reduce deformation caused by moisture changes during subsequent use.
[0043] Use 240-250 mesh abrasive belt for polishing. This mesh number of abrasive belt can make the substrate surface reach appropriate roughness and flatness. Sanding to the thickness deviation within 0.15mm can ensure the thickness uniformity of the substrate, which is very important for the subsequent processing and installation of decorative panels. The board surface is flat, with a finish of Ra0.7-0.9. This higher finish provides good surface conditions for subsequent composite or decorative processes, and also improves the appearance quality of the substrate, making the decorative panel more beautiful when it is finally used.
[0044] By obtaining formaldehyde-free plywood and formaldehyde-free blockboard substrates through secondary trimming, the size of the substrate can be precisely controlled. This can not only meet the diverse requirements for the size of decorative panels in different decoration scenarios, but also remove the unevenness and damage defects that may appear on the edge of the substrate during the early processing process, ensure the edge quality of the substrate, and make the decorative panels more convenient and beautiful during installation and splicing.
[0045] The curing period is set to 8-12 days. This process allows the substrate to fully release internal stress in a natural environment. After the previous processing steps, a certain amount of stress may accumulate inside the substrate. The curing process can release this stress, making the performance of the substrate more stable. After curing, the substrate can better adapt to the subsequent processing and use environment, reducing the possibility of deformation, warping and other problems during use.
[0046] Preferably, the formaldehyde-free substrate is hardened, and the specific steps include: S41 material preparation: The modified hard primer is a saturated polyester resin coating modified with silicone, which is compounded with acrylic paint, silicone, shielding agent and curing agent. The proportion of each component is: acrylic paint: silicone: shielding agent: curing agent = 100: 1-2: 3-6: 0.2-0.5; its main components are dimethyl diethyl silane, ethylene glycol, terephthalic acid, ion exchanger, silicone, magnesium silicate and polyisocyanate; S42 coating treatment: coating operation is carried out after curing of the formaldehyde-free substrate. The coating amount for the first coating is 30-40g / m²; S43 polishing: polishing with 240 mesh and 320 mesh combination abrasive belts to ensure a smooth and clean surface with a finish within Ra0.4-0.6 and a surface hardness of 2-4H; S44 curing and curing: the curing and curing time is set to 3-5 days; S45 coating treatment: After the substrate is first coated, polished, cured and solidified, a second coating is carried out, with a coating amount of 30-40g / m²; S46 polishing: polish the surface again, using a combination of 240-mesh and 320-mesh abrasive belts to further improve the surface quality, with a finish Ra of 0.4-0.5 and a surface hardness of 3-4H; S47 curing: set the number of days to 5-10 days to obtain hardened formaldehyde-free plywood and formaldehyde-free blockboard substrates.
[0047] Through a series of treatments such as coating, polishing and curing of silicone modified saturated polyester resin coating, the surface hardness of formaldehyde-free plywood and formaldehyde-free blockboard substrates is improved. From the initial surface hardness of 2-4H, after the second coating and polishing treatment, the surface hardness can reach 3-4H, which improves the wear resistance and scratch resistance of the board.
[0048] The surface finish was significantly improved by using a combination of 240-mesh and 320-mesh abrasive belts for multiple polishing processes. The finish was improved from Ra0.4-0.6 to Ra0.4-0.5, and the surface was smoother. This not only improved the appearance quality of the plate and made it more beautiful, but also facilitated the subsequent painting, veneer and other decorative treatments, making the subsequent coating or veneer smoother and firmer.
[0049] The modified hard primer can fill the tiny pores on the surface of the board to a certain extent, making the surface denser. This helps to improve the bonding performance of the board with other materials (such as finishing materials), making the bonding stronger, while also enhancing the structural stability of the board itself, reducing the possibility of delamination, cracking and other problems caused by external forces during use.
[0050] The increase in surface hardness directly leads to the enhancement of wear resistance and scratch resistance, so that the board can better resist external friction and scratches in daily use, and extend the service life of the board; good surface finish makes the appearance of the board more beautiful, in line with the requirements of modern decoration for material appearance quality, and can improve the market competitiveness of the product; it helps to improve the bonding quality of the board with other materials, while enhancing its own structural stability, ensuring the reliability of the performance of the board during use.
[0051] Preferably, the high surface performance formaldehyde-free paper is prepared by the following specific steps: S51 prepare raw materials: 76-82 parts of acrylic emulsion, 15-20 parts of melamine resin, 0.3-0.4 parts of catalyst p-toluenesulfonic acid, 0.12-0.18 parts of wetting agent, 0.1-0.13 parts of penetrant, 0.1-0.2 parts of defoamer, 3-8.2 parts of deionized water, pre-impregnated paper, and apply water-based paint; The pre-impregnated paper has a tensile strength of 40N / 10m-60N / 20m and a gram weight of 50-80g / m²; The water-based coating is water-based acrylic emulsion, water-based polyurethane or polyacrylate; Preparation of S52 water-based amino resin: S521 weigh a certain amount of melamine resin according to the ratio, add deionized water, and dilute the melamine resin to a mass fraction of 50-60%; S522 Add the diluted melamine resin into the quantitative acrylic emulsion, stir at 800-1200 rpm for 4-5 minutes, and then reduce the speed; S523 then add catalyst, wetting agent, penetrant, defoamer and other corresponding additives, stir evenly to obtain water-based amino resin for standby use; S53 roller coating process: S531 is roller coated using a specific coating roller, and the prepared water-based amino resin is injected between the coating rollers; The S532 pre-impregnated paper is horizontally unwound by an unwinder, and then coated with a water-based coating on the surface by a roller coater to obtain a surface coating; S533 is dried in a dryer to control the tensile strength of the pre-impregnated paper to be 40N / 10m-60N / 20m and the gram weight to be 50-80g / m², thereby obtaining formaldehyde-free facing paper with certain decorative properties and surface properties, namely the formaldehyde-free paper with high surface properties.
[0052] Pre-impregnated paper is a special industrial paper made of high-quality wood pulp and titanium dioxide as the main raw materials through a special process. It is an excellent environmentally friendly material that "replaces plastic and wood with paper" and has the characteristics of zero formaldehyde, no pollution, easy processing, and low energy consumption. Its production process usually involves partial carbonization of base paper fibers, external coating and internal infiltration treatment of plant-based pre-impregnated raw materials, and coating molding. Pre-impregnated paper has the advantages of strong abrasion resistance, stable color, and high light transmission and shielding ability.
[0053] Water-based coatings include water-based acrylic emulsions, water-based polyurethanes or polyacrylates. Water-based acrylic emulsions have good film-forming properties and have certain weather resistance and chemical corrosion resistance; water-based polyurethanes have a wide range of adjustable structures and properties, and have the advantages of being green and environmentally friendly, no formaldehyde release, fast drying speed, and good film-forming properties; polyacrylates can be used as topcoat varnish.
[0054] Water-based acrylic emulsion can form a continuous and uniform film on the coated surface, which is very important for protecting and decorating the coated material. Pre-impregnated paper is used for formaldehyde-free decorative panels. Good film-forming properties can make the surface smoother and smoother, improve the appearance quality, and better block the erosion of the material by the external environment; and it has a certain ability to resist climate change, including tolerance to sunlight, temperature changes, humidity changes, etc. Under different climatic conditions, it can maintain good performance and is not prone to fading, cracking, peeling and other problems, thereby extending the service life of the formaldehyde-free decorative panel and making it suitable for a variety of indoor and outdoor environments; it can resist the erosion of some chemicals, making the formaldehyde-free decorative panels coated with water-based acrylic emulsion more durable during cleaning and maintenance, and not easily damaged by chemicals.
[0055] Waterborne polyurethane can adjust its performance by changing its molecular structure and composition to meet different application requirements. Its hardness, flexibility, wear resistance, adhesion and other properties can be adjusted to enable it to better adapt to different use scenarios and requirements of formaldehyde-free decorative panels. According to needs, waterborne polyurethane coatings with both high hardness to resist scratches and certain flexibility to adapt to material deformation can be prepared; it meets environmental protection requirements and does not release harmful gases such as formaldehyde during use, which is harmless to indoor air quality and human health. This is especially important for formaldehyde-free decorative panels, which are materials used for interior decoration, and can meet people's needs for healthy and environmentally friendly decoration materials; waterborne polyurethane has a fast drying speed and good film-forming properties. The fast drying speed can improve production efficiency and reduce production cycles. At the same time, good film-forming properties can ensure the coating effect, make the surface smooth and uniform, and improve the appearance quality and protective performance of formaldehyde-free decorative panels.
[0056] Polyacrylate as top coating varnish can provide a high-gloss surface effect, making the formaldehyde-free decorative panels look brighter and more beautiful, improving the decorativeness of the product. At the same time, it can protect the underlying coatings and materials to a certain extent and prevent them from external damage.
[0057] Water-based amino resin is a formaldehyde-free adhesive. From the perspective of its raw material composition, it mainly includes acrylic emulsion, melamine resin, catalyst benzenesulfonic acid, wetting agent, penetrant, defoamer, deionized water, etc. These raw materials do not contain formaldehyde and meet the requirements of formaldehyde-free. There is a specific ratio range between the raw materials such as acrylic emulsion and melamine resin. This reasonable ratio enables the various components to work synergistically and exert good performance. Melamine resin can provide better hardness and wear resistance, while acrylic emulsion can give flexibility and good bonding properties. 4-Benzenesulfonic acid is a strong aromatic acid that can provide an acidic environment. In the process of preparing water-based amino resin, adding 4-benzenesulfonic acid can promote the reaction between melamine resin and acrylic emulsion, accelerate the reaction process, and make the reaction more sufficient and efficient. Through its acidic catalytic effect, the rate and degree of the reaction can be adjusted to ensure that the water-based amino resin can be prepared according to the expected formula and performance requirements, control the reaction time and the structure and performance of the reaction product, so that the final water-based amino resin has suitable molecular weight, viscosity and other properties, so as to facilitate the subsequent roller coating process. In the process of preparing formaldehyde-free paper, the presence of 4-benzenesulfonic acid can help improve the performance stability of the product, promote the interaction and cross-linking reaction between the components, and make the surface coating of the formaldehyde-free paper have better adhesion, wear resistance, water resistance and other properties, thereby improving the overall quality and service life of the formaldehyde-free decorative panel.
[0058] In the mixing process, first dilute the melamine resin and add it to the acrylic emulsion for 4-5 minutes at 800-1200 rpm, then reduce the speed and add other additives to mix evenly. High-speed stirring can fully mix the components to ensure the formation of a uniform system and avoid performance differences caused by uneven local components. The fully mixed resin can stably exert its bonding and surface treatment properties during use.
[0059] Compared with the resins available on the market, the water-based amino resin prepared by this process clearly does not contain formaldehyde, has better environmental performance, and meets the modern strict requirements for formaldehyde-free products, especially in application scenarios such as interior decoration, which can better protect human health. Due to its reasonable formula design and sufficient mixing process, it has advantages in bonding performance, can better adapt to the surface characteristics of substrates and finishing materials, and provide more uniform bonding strength. When this resin is used to prepare formaldehyde-free decorative panels, it can give the decorative panels certain decorative properties and surface properties. It can form a good surface coating on pre-impregnated paper through a roller coating process to improve the surface finish and wear resistance and other properties. Existing resins are not as good as this water-based amino resin in surface treatment performance, and cannot achieve the same decorative effect and surface quality.
[0060] Preferably, the formaldehyde-free decorative panel is compositely produced, and the specific steps include: S61 Dust Removal: The substrate is subjected to three dust removal processes: electrostatic, brush and air blowing; S62 glue coating and lamination: The glue coating uses polyvinyl acetate or polyurethane formaldehyde-free fast curing adhesive, and the glue coating amount is 30-40g / m 2 , the board feeding speed is 10-20 meters per minute, the tension of the formaldehyde-free paper support roller is 9-12N / m, and the paper tension modulation is 10-20N / 10-20mm; S63 Roller Pressing: Set the roller pressing pressure to 0.7-0.9 mm and the time to 2-10 minutes; S64 trimming: trims excess paper edges to ensure consistent size; S65 curing and curing: set the curing and curing time to 24-48 hours to obtain the new formaldehyde-free decorative panel.
[0061] The three dust removal processes of electrostatic, brush and air blast are used to treat the substrate, which can effectively remove dust, wood chips and other impurities on the surface of the substrate. Electrostatic dust removal can absorb tiny charged particles, brush dust removal can sweep away larger impurities, and air blast dust removal can blow away loosely attached dust. These three processes work together to provide a very clean substrate surface for subsequent glue coating and lamination. A clean surface is conducive to the uniform adhesion of glue, avoiding the presence of impurities that cause the glue to be loosely bonded, thereby improving the composite quality of the veneer.
[0062] The glue used is polyvinyl acetate or polyurethane formaldehyde-free fast-curing adhesive, both of which are formaldehyde-free and meet the environmental protection requirements of decorative panels. Polyvinyl acetate adhesive has good bonding performance and flexibility, and can adapt to the slight deformation of different wood surfaces, making the bond between the decorative paper and the substrate more firm and durable. Polyurethane adhesive has high bonding strength and excellent water resistance and weather resistance. It can also ensure the stability of the composite structure of the decorative panel in a humid environment or when the temperature changes greatly.
[0063] The glue coating amount is 30-40g / m². This appropriate glue coating amount can ensure good bonding between the facing paper and the substrate while avoiding excessive glue overflow, which affects the appearance and quality of the facing board. The board feeding speed is 10-20 meters per minute. This speed allows the glue to have appropriate time for preliminary diffusion and penetration before entering the rolling process, while ensuring production efficiency.
[0064] The tension of the formaldehyde-free paper support roller is 9-12N / m. This tension range can keep the facing paper flat during the gluing and laminating process, preventing wrinkles or stretching deformation of the facing paper. Flat facing paper can better fit the substrate, ensure the surface flatness of the facing board, and improve the decorative effect and quality of the facing board.
[0065] Set the rolling pressure to 0.7-0.9mm and the time to 2-10 minutes. This combination of pressure and time can make the facing paper and the substrate fit tightly under the action of glue. The appropriate pressure can squeeze the glue evenly between the two, exclude air, and avoid bubbles or hollowing. The appropriate rolling time can ensure that the glue is fully cured, improve the bonding strength, make the composite structure of the veneer more stable, and thus extend the service life of the veneer.
[0066] Cutting off the excess rough edges of the paper and ensuring the same size can make the edges of the decorative panels neat and beautiful. During the decoration process, decorative panels with the same size are easier to splice and install, which can improve construction efficiency and make the final decorative effect more neat and standardized, meeting the requirements of modern decoration for precision and beauty.
[0067] The curing time is set to 24-48 hours. This process allows the glue to fully cure inside the veneer. After the previous rolling process, although the glue has been initially bonded, it will take some time to reach the optimal curing state. During the curing period, the molecular structure of the glue will be further stabilized, making the bond between the veneer paper and the substrate stronger, improving the overall strength and stability of the veneer, and ensuring that the veneer will not have quality problems such as veneer paper falling off during long-term use.
[0068] In summary, the present invention has the following beneficial effects: 1. Compared with the prior art, the formaldehyde-free decorative panel and the preparation method thereof provided by the present invention are safe and environmentally friendly; formaldehyde-free is achieved from the substrate to the facing paper, avoiding the pollution of indoor environment by formaldehyde release and protecting the health of residents; the substrate is prepared by using formaldehyde-free adhesive modified acrylic resin glue to eliminate formaldehyde from the source; the facing paper is improved pre-impregnated paper, which also does not contain formaldehyde; formaldehyde-free materials and environmentally friendly processes are selected in the entire preparation process, and the preparation and use of formaldehyde-free adhesives avoid the problem of formaldehyde release of traditional adhesives; formaldehyde-free raw materials such as water-based amino resins are used in the preparation of high surface performance formaldehyde-free paper, which meets environmental protection requirements; 2. Compared with the existing impregnated film paper veneer artificial board and pre-impregnated paper veneer artificial board, the formaldehyde-free veneer panel of the present invention has high strength and stability. The formaldehyde-free plywood and formaldehyde-free blockboard are used as the base substrate. Through reasonable combination and processing, the structural advantages of plywood and blockboard are complemented by a specific pressing process, and the deformation resistance is enhanced. The base substrate has a reasonable structure, and its internal multi-layer structure and core material-veneer structure cooperate with each other to provide a solid foundation for the veneer panel, which can withstand daily collisions, extrusion and other external forces without being easily damaged; the balancing layer adopts formaldehyde-free poplar bleached veneer or high-density fiberboard, which improves the overall structural performance of the base substrate, making it more durable and more resistant to deformation and external force damage; the improved pre-impregnated paper has a certain tear resistance after special treatment; the formaldehyde-free veneer panel prepared by the present invention has richer colors and textures, There are synchronous pattern, skin feeling, zero degree, high gloss and other pattern textures, which change the surface display form of pre-impregnated paper veneer with only flat matte effect, expand the application scenes and fields, and can provide a variety of decorative effects at the same time, meet the needs of different decoration styles, and provide rich choices for interior decoration; in the process of substrate production and veneer composite production, secondary trimming and multiple trimming operations of cutting off excess burrs of paper can accurately control the size, ensure the consistent size of veneer panels, neat and beautiful edges, meet the size requirements of different decoration scenes, and make the veneer panels more convenient to install and splice, improve construction efficiency, and ensure the neatness and standardization of the final decorative effect; the formaldehyde-free veneer panels prepared by the present invention adopt flat pasting process, which is efficient and low-consumption, and the veneer production efficiency is higher than that of impregnated film paper veneer artificial boards, and the production energy consumption is much lower than that of existing veneers, which is efficient and low-consumption; 3. The production process of the present invention is advanced and efficient. From the preparation of formaldehyde-free adhesive, the preparation of substrate and formaldehyde-free paper separately to the final composite production, each step has been carefully designed and optimized, and each link is interconnected to ensure the smooth progress of the entire production process and improve production efficiency and product quality. In each process flow, various parameters such as temperature, pressure, time, and glue coating amount are strictly controlled and optimized. The control of reaction temperature, stirring speed and time in the preparation of formaldehyde-free adhesive ensures the excellent performance of the adhesive. The setting of glue coating amount, cold pressing and hot pressing parameters in the process of substrate production ensures the gluing quality and stable performance of the substrate. The surface hardening pretreatment technology of the substrate is applied to paper decorative panels for the first time, which greatly improves the board surface effect, significantly improves the surface hardness, and significantly reduces the surface wear resistance value compared with traditional decorative panels, and improves the surface scratch resistance. The control of parameters such as glue coating amount, roller pressure and time in the composite production of decorative panels improves the composite quality and production efficiency. 4. The adhesive technology in the method for preparing the decorative panel of the present invention is innovative, and a new formaldehyde-free adhesive such as a modified acrylic resin adhesive is used, which has good bonding performance, flexibility, water resistance and weather resistance; the formula design is reasonable, and by adding specific fillers and humidity-adjusting materials, reacting under nitrogen protection, and fully mixing the components, the adhesive performance is better than the common formaldehyde-free adhesive on the market, better adapts to the surface characteristics of the substrate and the decorative material, provides a more uniform bonding strength, and reduces the cost at the same time; 5. The method for preparing the decorative panel of the present invention applies polymer surface treatment technology. In the hardening treatment of the formaldehyde-free substrate and the preparation of formaldehyde-free paper with high surface performance, polymer materials such as silicone-modified saturated polyester resin coatings and water-based amino resins and related technologies are applied. By hardening the substrate, the surface hardness and smoothness are improved, and the wear resistance and scratch resistance are enhanced. The water-based amino resin plays an important role in the preparation of formaldehyde-free paper, giving the formaldehyde-free paper good decorative properties and surface properties, so that it has better gluing properties and surface quality. 6. During the entire preparation process, the hot pressing and other processes in the production of formaldehyde-free plywood and formaldehyde-free blockboard substrates adopt low-temperature and low-pressure processes. The low-temperature bonding and low-energy production technology reduces energy consumption, has a great energy-saving effect, and meets the requirements of sustainable development; at the same time, the low-temperature process also reduces the impact on material properties and ensures product quality; 7. The composite production of formaldehyde-free decorative panels adopts advanced methods such as flat lamination technology, which can quickly and accurately laminate the formaldehyde-free substrate and the formaldehyde-free paper with high surface performance; the reasonable board feeding speed and glue amount control in the glue lamination process, as well as the appropriate pressure and time setting in the roller pressing process, not only ensure the product quality, but also improve the production efficiency, help reduce production costs, make the formaldehyde-free decorative panels more competitive in the market, and meet the growing market demand for environmentally friendly decorative materials; 8. The entire preparation process is reasonably designed, and each process is standardized, which makes it easy to achieve large-scale production. Through precise parameter control and the application of advanced equipment and technology, the stability and consistency of product quality can be guaranteed during large-scale production, thereby improving production efficiency, reducing production costs, and providing the market with sufficient formaldehyde-free decorative panel products. DETAILED DESCRIPTION
[0069] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
[0070] Example 1
[0071] Preparation of S1 formaldehyde-free adhesive: firstly, 20 parts of acrylic acid monomer, 50 parts of acrylate monomer and 60 parts of deionized water were mixed, and then 10 parts of hydroxyl functional body, 6 parts of polyvinyl alcohol, 2 parts of emulsifier and 0.02 parts of initiator were added, and the mixture was reacted for 4 hours at 60°C and 500 rpm under nitrogen protection to obtain a modified acrylic resin emulsion; with the obtained modified acrylic resin emulsion as the main body, a part of flour was added as filler, and a certain amount of humidifying material calcium chloride or magnesium chloride was added, and the mixture was stirred at 500 rpm for 12 minutes to obtain a formaldehyde-free adhesive; modified acrylic resin emulsion: flour: humidifying material = 100:20:1; Preparation of S2 formaldehyde-free plywood and formaldehyde-free blockboard substrate: The feed ratio is: fir board core: eucalyptus short core = 5:4, the amount of formaldehyde-free adhesive is 170g / m², and the blanks are assembled in a criss-cross pattern according to the design plan, and the gluing time is controlled within 50 minutes; the cold pressing time is set to 60 minutes, and the pressure is 0.85MPa; cut off the overlap and fill the missing core gap; the temperature is 125℃, the time is 30 minutes, and the pressure is 0.75MPa, and hot pressing is performed until the moisture content of the blank is 9%. The moisture content deviation is 1.6%; the blank is hot pressed within 12 hours after cold pressing; a combination of 60 and 120 mesh sanding belts is selected, and the board is sanded to a specified thickness of 15.8 mm, the thickness deviation within the board is within 0.2 mm, and the board surface finish is Ra1.6; the core missing parts of the flat surface are filled with putty; the formaldehyde-free plywood and formaldehyde-free blockboard substrates are obtained by trimming the edges once, with a specification of 1240*2460 mm; the curing period is 8 days, and the formaldehyde-free plywood and formaldehyde-free blockboard substrates are obtained; S3 formaldehyde-free plywood and formaldehyde-free blockboard substrate production: a 1.0mm high-density fiberboard balance layer is laminated on the top and bottom of the 15.8mm formaldehyde-free blockboard substrate, and the formaldehyde-free adhesive coating amount is 150g / m 2, the gluing time is controlled within 40 minutes; cold pressing within 40 minutes, the pressure is 0.75MPa; the hot pressing temperature is set to 120℃, the time is 10 minutes, the pressure is 0.7MPa, and the moisture content after hot pressing is controlled to be 8%; 240 mesh sanding belt is used for polishing, and the thickness deviation of the board is sanded to 0.15mm, the board surface is flat, and the finish is Ra0.8; the second trimming is performed to obtain the formaldehyde-free plywood and formaldehyde-free blockboard substrate, and the specifications after trimming are 1220*2440mm; the curing days are set to 10 days to obtain the formaldehyde-free plywood and formaldehyde-free blockboard substrate; S4 formaldehyde-free substrate hardening treatment: The components and proportions of the modified hardened primer are: acrylic paint: silicone: masking agent: curing agent = 100:2:6:0.5; the coating operation is carried out after the formaldehyde-free substrate is cured, and the coating amount is 40g / m² for the first coating; a 240-mesh and 320-mesh combined sanding belt is used for polishing to ensure that the surface is flat and smooth; the curing and curing time is set to 5 days; after the first coating, polishing and curing of the substrate, the second coating is carried out, and the coating amount is 40g / m²; the surface is polished again, and a 240-mesh and 320-mesh combined sanding belt is used for polishing to further improve the surface quality; the curing days are set to 10 days, and the hardened formaldehyde-free plywood and formaldehyde-free blockboard substrates are obtained; S5 Preparation of formaldehyde-free paper with high surface performance: 20 parts of melamine resin are weighed according to the ratio, and 8.2 parts of deionized water are added to dilute the melamine resin to a mass fraction of 60%; the diluted melamine resin is added to 82 parts of acrylic emulsion, and stirred at a high speed of 1200 rpm for 5 minutes, and then the speed is reduced; then 0.4 parts of p-toluenesulfonic acid catalyst, 0.18 parts of wetting agent, 0.13 parts of penetrant, 0.2 parts of defoamer and various corresponding additives are added, and the water-based amino resin is obtained after stirring evenly, and it is set aside; a specific coating roller is used for roller coating, and the prepared water-based amino resin is injected between the coating rollers; the pre-impregnated paper is horizontally unwound by an unwinder, and the surface is coated with a water-based coating after passing through a roller coater to obtain a surface coating; it is dried in a dryer, and the tensile strength of the pre-impregnated paper is controlled to be 60N / 10m and the gram weight is 80g / m², so as to obtain a formaldehyde-free facing paper with certain decorative properties and surface properties, that is, the formaldehyde-free paper with high surface performance; S6 formaldehyde-free veneer composite production: the substrate is subjected to three dust removal processes: static electricity, brush and air blowing; the glue coating uses polyurethane formaldehyde-free fast curing adhesive, and the glue coating amount is 35g / m 2 , the board feeding speed is 20 meters per minute, the tension of the formaldehyde-free paper support roller is 12N / m, and the paper tension is modulated to 20N / 10mm; the roller pressure is set to 0.8mm and the time is 2 minutes; the excess burrs of the paper are cut off to ensure consistent size; the curing time is set to 48 hours to obtain the new formaldehyde-free decorative panel.
[0072] Example 2
[0073] Preparation of S1 formaldehyde-free adhesive: firstly, 20 parts of acrylic acid monomer, 50 parts of acrylate monomer and 60 parts of deionized water were mixed, and then 10 parts of hydroxyl functional body, 6 parts of polyvinyl alcohol, 2 parts of emulsifier and 0.02 parts of initiator were added, and the mixture was reacted for 4 hours at 60°C and 500 rpm under nitrogen protection to obtain a modified acrylic resin emulsion; with the obtained modified acrylic resin emulsion as the main body, a part of flour was added as filler, and a certain amount of humidifying material calcium chloride or magnesium chloride was added, and the mixture was stirred at 500 rpm for 15 minutes to obtain a formaldehyde-free adhesive; modified acrylic resin emulsion: flour: humidifying material = 100:22:1; Preparation of S2 formaldehyde-free plywood and formaldehyde-free blockboard substrate: the feed ratio is: eucalyptus short core: eucalyptus long core = 5:4, the amount of formaldehyde-free adhesive is 160g / m², the blanks are assembled in a criss-cross pattern according to the design plan, and the gluing time is controlled within 50 minutes; the cold pressing time is set to 60 minutes, the pressure is 0.85MPa; the overlap is cut off, and the missing core gap is filled; the temperature is 125℃, the time is 30 minutes, the pressure is 0.8MPa, and the moisture content of the blank is hot pressed to 9%. The moisture content deviation is 1.7%; the blank is hot pressed within 12 hours after cold pressing; a combination of 60 and 120 mesh sanding belts is selected, and the board is sanded to a specified thickness of 15.8 mm, the thickness deviation within the board is within 0.2 mm, and the board surface finish is Ra1.6; the core missing parts of the flat surface are filled with putty; the formaldehyde-free plywood and formaldehyde-free blockboard substrates are obtained by trimming the edges once, with a specification of 1240*2460 mm; the curing period is 7 days, and the formaldehyde-free plywood and formaldehyde-free blockboard substrates are obtained; S3 formaldehyde-free plywood and formaldehyde-free blockboard substrate production: a 1.0mm high-density fiberboard balance layer is laminated on the top and bottom of the 15.8mm formaldehyde-free plywood substrate, and the formaldehyde-free adhesive coating amount is 150g / m 2 , the gluing time is controlled at 40 minutes; other operations are the same as step S3 of Example 1, to obtain the formaldehyde-free plywood and formaldehyde-free blockboard substrate; Steps S4, S5 and S6 are the same as those in Example 1 to obtain the novel formaldehyde-free decorative panel.
[0074] Example 3
[0075] Steps S1, S2, and S3 are the same as those in Example 1; S4 formaldehyde-free substrate hardening treatment: The components and proportions of the modified hardened primer are as follows: acrylic paint: silicone: masking agent: curing agent = 80:1:3:0.2; the coating operation is carried out after the formaldehyde-free substrate is cured, and the coating amount for the first coating is 30g / m²; a 240-mesh and 320-mesh combined sanding belt is used for polishing to ensure that the surface is flat and smooth, with a finish Ra0.4; the curing and curing time is set to 3 days; after the first coating, polishing and curing of the substrate, a second coating is carried out, with a coating amount of 30g / m²; the surface is polished again, and a 240-mesh and 320-mesh combined sanding belt is used for polishing to further improve the surface quality, and the finish Ra reaches 0.4; the curing days are set to 5 days, and the hardened formaldehyde-free plywood and formaldehyde-free blockboard substrates are obtained; S5 Preparation of formaldehyde-free paper with high surface performance: 15 parts of melamine resin are weighed according to the ratio, and 3 parts of deionized water are added to dilute the melamine resin to a mass fraction of 50%; the diluted melamine resin is added to 76 parts of acrylic emulsion, and stirred at a high speed of 800 rpm for 4 minutes, and then the speed is reduced; then 0.3 parts of p-toluenesulfonic acid catalyst, 0.12 parts of wetting agent, 0.1 parts of penetrant, 0.1 parts of defoamer and various corresponding additives are added, and the water-based amino resin is obtained after uniform stirring, and is set aside; a specific coating roller is used for roller coating, and the prepared water-based amino resin is injected between the coating rollers; the pre-impregnated paper is horizontally unwound by an unwinder, and the surface is coated with a water-based coating after passing through a roller coater to obtain a surface coating; it is dried in a dryer, and the tensile strength of the pre-impregnated paper is controlled to be 40N / 10m and the gram weight is 50g / m², so as to obtain a formaldehyde-free facing paper with certain decorative properties and surface properties, that is, the formaldehyde-free paper with high surface performance; S6 formaldehyde-free veneer composite production: the substrate is subjected to three dust removal processes: static electricity, brush and air blowing; the glue coating uses polyurethane formaldehyde-free fast curing adhesive, and the glue coating amount is 35g / m 2 , the board feeding speed is 10 meters per minute, the tension of the formaldehyde-free paper support roller is 9N / m, and the paper tension is modulated to 10N / 20mm; the roller pressure is set to 0.8mm and the time is 10 minutes; the excess burrs of the paper are cut off to ensure consistent size; the curing time is set to 24 hours to obtain the new formaldehyde-free decorative panel.
[0076] Example 4
[0077] Preparation of S1 formaldehyde-free adhesive: first mix 25 parts of acrylic acid monomer, 60 parts of acrylate monomer and 90 parts of deionized water, then add 16 parts of hydroxyl functional body, 10 parts of polyvinyl alcohol, 4 parts of emulsifier and 0.6 parts of initiator, and continue to react at 80°C and 800 rpm for 6 hours under nitrogen protection to obtain modified acrylic resin emulsion; with the prepared modified acrylic resin emulsion as the main body, add a part of flour as filler, supplemented with a certain amount of humidifying material calcium chloride or magnesium chloride, and stir at 3000 rpm for 15 minutes to obtain formaldehyde-free adhesive; modified acrylic resin emulsion: flour: humidifying material = 100:25:1.
[0078] The remaining steps are the same as those in Example 1 to obtain the novel formaldehyde-free decorative panel.
[0079] Example 5
[0080] Preparation of S1 formaldehyde-free adhesive: firstly, 20 parts of acrylic acid monomer, 50 parts of acrylate monomer and 60 parts of deionized water were mixed, and then 10 parts of hydroxyl functional body, 5 parts of polyvinyl alcohol, 2 parts of emulsifier and 0.2 parts of initiator were added, and the mixture was reacted for 2 hours at 40°C and 300 rpm under nitrogen protection to obtain a modified acrylic resin emulsion; with the obtained modified acrylic resin emulsion as the main body, a part of flour was added as filler, and a certain amount of humidifying material calcium chloride or magnesium chloride was added, and the mixture was stirred at 500 rpm for 10 minutes to obtain a formaldehyde-free adhesive; modified acrylic resin emulsion: flour: humidifying material = 80:20:0.5; The remaining steps are the same as those in Example 1 to obtain the novel formaldehyde-free decorative panel.
[0081] Comparative Example 1 Ordinary pre-impregnated paper is flatly pasted on ENF-grade ecological board to obtain a traditional veneer.
[0082] 1. Experimental Methods A series of performance tests were conducted on the decorative panels prepared in Examples 1-5 and Comparative Example 1, including indicators such as formaldehyde emission, bonding strength, surface bonding strength, surface wear resistance, and surface hardness.
[0083] 1.1 Formaldehyde emission The test is conducted in accordance with GB / T 39600-2021 "Classification of Formaldehyde Emissions from Artificial Boards and Their Products" and T / CNFPIA 1003-2022. These two standards set clear classification requirements and testing specifications for the formaldehyde emissions of artificial boards and their products from different perspectives, ensuring the scientificity and accuracy of the test results, and being able to fully reflect the formaldehyde emissions of products in different usage environments.
[0084] The test is carried out under specific temperature conditions, and two temperature nodes of 23°C and 30°C are set respectively. The prepared sample of the embodiment of the present invention and the sample of the control group (ordinary pre-impregnated paper flatly pasted on the ENF-grade ecological board) are placed in an environmental chamber that meets the standard requirements. The temperature, humidity, air flow rate and other conditions in the environmental chamber are strictly controlled in accordance with the standard provisions. Within the specified time interval, the formaldehyde concentration in the air in the environmental chamber is continuously monitored and data is collected through professional formaldehyde detection instruments, such as mature detection technologies such as spectrophotometry or gas chromatography. After a certain period of stabilization, the formaldehyde release of the sample at different temperatures is accurately calculated based on the collected data and the calculation formula in the corresponding standard.
[0085] 1.2 Bonding strength The test is carried out in accordance with GB / T 34722-2017 "Impregnated Paper Laminated Wood Flooring". This standard sets detailed technical requirements and test specifications for the bonding strength of wood flooring and other similar products. Although the product of the present invention may not be completely wood flooring, the test method and judgment criteria for bonding strength are universal and can objectively evaluate the firmness of the bonding connection between the layers of the product.
[0086] Testing method: First, cut a specimen of specified size and shape from the prepared sample to ensure that the specimen is representative and meets the size specifications required by the standard. Then, fix the specimen on a professional bonding strength test device and apply a gradually increasing tensile force to the specimen to simulate the external force that may be applied during actual use until the bonding part of the specimen is damaged. During the test, the equipment will record the magnitude of the tensile force and the state of the bonding part of the specimen when it is damaged in real time. Finally, according to the calculation formula specified in the GB / T 34722-2017 standard and the data collected during the test, the bonding strength value of the sample is accurately calculated.
[0087] 1.3 Surface bonding strength The test is also based on GB / T 34722-2017 "Impregnated Paper Laminated Wood Flooring" standard. This standard also has clear provisions for the test of surface bonding strength. Through unified standards and specifications, the performance differences of different samples in surface bonding can be compared fairly and accurately.
[0088] Similar to the bonding strength test, first make a specific specimen that meets the standard size requirements from the sample. Place the specimen on a device specifically used for surface bonding strength testing. The device usually uses a specific fixture and loading device to accurately apply a tensile force perpendicular to the surface to the bonding part of the specimen surface. During the test, the tensile force is gradually increased until the bonding layer on the surface of the specimen is damaged. During this period, the equipment continuously records the tensile force value and related conditions at the time of damage. Finally, according to the calculation method specified in the GB / T 34722-2017 standard, the surface bonding strength index of the sample is calculated based on the test data.
[0089] 1.4 Surface wear resistance The test is carried out in accordance with GB / T 34722-2017 "Impregnated Paper Laminated Wood Flooring". This standard sets detailed evaluation indicators and testing procedures for the surface wear resistance of products such as wood floors, and can be used for comparative testing of the surface wear resistance of the sample of the present invention and the sample of the control group.
[0090] Select a certain area of the sample surface as the test area, and fix the sample on a professional surface wear test equipment, such as the Taber abrasion tester. Install a specified model of grinding wheel on the test equipment, and perform the test operation according to the load, speed, friction number and other parameters set in the standard. After the grinding wheel rubs the sample surface for a certain number of times, the surface wear depth, weight loss or appearance change of the sample surface is measured, and the surface wear resistance of the sample is quantitatively evaluated according to the judgment rules in the GB / T 34722-2017 standard to determine its surface wear grade or specific wear resistance value.
[0091] 1.5 Surface hardness The test is carried out in accordance with GB / T 37005-2018 "Test Method for Surface Hardness of Wooden Floors". This standard specifically formulates a scientific and reasonable test method and evaluation system for the surface hardness test of wooden floors, and is also of reference value and applicability for the surface hardness test of products such as decorative panels involved in this invention.
[0092] First, select appropriate test points on the surface of the sample to ensure that the test points are evenly distributed and representative. Then, use a professional surface hardness testing instrument to press the indenter of the Shore D hardness tester vertically on the test point and operate according to the pressure application method and holding time specified in the standard. The hardness tester will automatically read and record relevant data such as the depth or rebound force of the indenter pressed into the sample surface. According to the calculation formula and judgment criteria in the GB / T 37005-2018 standard, the surface hardness value of the sample is calculated based on these test data, thereby accurately evaluating the surface hardness performance of the sample.
[0093] 2. Experimental results The test results of formaldehyde emission, bonding strength, surface bonding strength, surface wear resistance, surface hardness and other indicators of the decorative panels prepared in Examples 1-5 and Comparative Example 1 are shown in the table below.
[0094] Table 1 Comparison of performance test of veneer panels prepared in each group
[0095] 2.1 Analysis of formaldehyde release It can be seen from the table that under the two temperature conditions of 23°C and 30°C, the formaldehyde emission of Examples 1-5 is significantly lower than that of Comparative Example 1. At a lower temperature of 23°C, the formaldehyde emission of Examples 1-5 is between 0.006-0.008 mg / m³, while the formaldehyde emission of Comparative Example 1 is 0.021 mg / m³; at 30°C, the formaldehyde emission of the Examples increases, but still remains at a low level of 0.012-0.018 mg / m³, while Comparative Example 1 increases significantly to 0.132 mg / m³. This shows that the decorative panels of the Examples can better control formaldehyde release under different temperature environments, especially when the temperature rises, and have more stable low formaldehyde emission performance.
[0096] From the data of formaldehyde emission, Examples 1-5 all showed extremely low formaldehyde emission levels at the detection temperatures of 23°C and 30°C. Compared with Comparative Example 1, the formaldehyde emission of the Examples was greatly reduced. This means that the decorative panels prepared by the present invention have significant advantages in environmental performance and can meet more stringent environmental standards, especially in indoor environments, whether at room temperature or slightly higher temperatures, and can effectively reduce the potential harm of formaldehyde to human health.
[0097] It is worth noting that as the temperature rises from 23°C to 30°C, the formaldehyde emission of the embodiment increases, but the increase is small and still at a low level. This shows that the formaldehyde emission of the decorative panel of the present invention is relatively stable under different temperature environments, and there will be no large-scale formaldehyde release due to temperature changes, which further reflects the reliability of its environmental performance.
[0098] 2.2 Wear value analysis The abrasion value is a key indicator for measuring the wear resistance of the surface of the decorative panel. The abrasion values of Examples 1-5 are much lower than that of Comparative Example 1, which shows that the decorative panel prepared by the present invention has excellent wear resistance. The lower abrasion value helps the decorative panel maintain its decorative effect and functional integrity during long-term use. The abrasion values of Examples 1-5 are between 40-43 mg / 100r. In contrast, the abrasion value of Comparative Example 1 is higher, reaching 132 mg / 100r, indicating that its surface is more easily worn, and scratches, discoloration and other problems may appear more quickly, affecting its appearance and performance. It shows that the surface wear resistance of the decorative panel of the embodiment is significantly better than that of the comparative example. After the same friction test, the degree of wear on the surface of the decorative panel of the embodiment is much smaller, and the surface integrity and aesthetics can be better maintained.
[0099] The wear values of the embodiments are relatively stable with a small fluctuation range, which reflects the consistency of the embodiments in terms of wear resistance. It shows that the method for preparing formaldehyde-free decorative panels of the present invention adopts a relatively stable preparation process and material formula, so that the surface wear resistance of the decorative panels can be effectively controlled and guaranteed.
[0100] 2.3 Surface hardness analysis From the data of surface hardness, the surface hardness values of Examples 1-5 are significantly higher than those of Comparative Example 1. The surface hardness of the embodiments ranges from 80 to 88, while that of Comparative Example 1 is only 50. This significant difference indicates that the decorative panels prepared by the present invention have greatly improved surface hardness. Higher surface hardness helps to improve the durability of the decorative panels. In contrast, the lower surface hardness of Comparative Example 1 makes it more prone to surface defects such as scratches and dents, which may further expand over time and affect the service life of the decorative panels. Due to the high surface hardness, the decorative panels of the present invention can maintain a good surface state for a long time, reduce the frequency of maintenance and replacement, and are of great significance for improving the economy and practicality of the product. This shows that the decorative panels prepared by the present invention have significant advantages in surface hardness, can better resist external pressure, friction and scratches, and thus more effectively maintain the integrity and aesthetics of the surface in daily use.
[0101] The surface hardness of the embodiment is maintained within a relatively high and concentrated range as a whole. This shows that the preparation process of the present invention has a certain stability in controlling the surface hardness. This stability can be achieved by optimizing the selection of raw materials and quality control, as well as accurate production process parameter setting, to ensure the consistency and reliability of product quality.
[0102] 2.4 Analysis of bonding strength and surface bonding strength From the test results, the bonding strength (average value) and surface bonding strength (average value) of Examples 1-5 are generally higher than those of Comparative Example 1. The average bonding strength of the Examples is between 1.12-1.21, and the average surface bonding strength is between 1.02-1.08, while the bonding strength of Comparative Example 1 is 0.72 and the surface bonding strength is 0.61. This shows that the veneer panels of the Examples perform better in terms of bonding, and the bonding strength between the layers is higher, which can better resist the problems of delamination and peeling that may occur during use, thereby ensuring the overall quality and service life of the veneer panels. The bonding strength and surface bonding strength between the Examples are also relatively stable, which shows that the preparation process of the Examples can ensure a relatively consistent quality level in the bonding link, which is conducive to mass production and quality control of the products.
[0103] Higher bonding strength and surface bonding strength help ensure the structural integrity of the veneer. In daily use, the veneer can better withstand external forces such as collision and extrusion, reduce the occurrence of quality problems such as delamination and debonding, thereby extending the service life of the veneer and improving the reliability and practicality of the product.
[0104] Experiments show that compared with the comparative example, the decorative panel of the embodiment performs better in terms of performance indicators such as formaldehyde emission, bonding strength, surface bonding strength, surface wear resistance and surface hardness. The present invention integrates multiple technologies to provide a method for preparing a decorative panel with formaldehyde-free, high surface performance and low carbon emissions. The decorative panel is composed of a formaldehyde-free substrate and formaldehyde-free facing paper. Through detailed process steps and precise process parameter control, excellent performance is achieved, and it has significant advantages in environmental protection, production efficiency, surface performance, etc.
Claims
1. A formaldehyde-free decorative panel, characterized in that: Specifically include: Formaldehyde-free substrate and formaldehyde-free facing paper; The formaldehyde-free substrate includes formaldehyde-free plywood and formaldehyde-free blockboard; The formaldehyde-free facing paper is improved pre-impregnated paper; The formaldehyde-free decorative panel is produced by compounding a formaldehyde-free base plate and a formaldehyde-free decorative paper using a flat-pasting process.
2. A formaldehyde-free decorative panel according to claim 1, characterized in that: The formaldehyde-free substrate specifically comprises: a substrate layer, a balancing layer and a hardened base coating layer; The substrate layer is made of one or two formaldehyde-free core wood panels and eucalyptus core panels using formaldehyde-free adhesives through gluing, assembly, cold pressing, core trimming, hot pressing, thickness sanding, edge trimming, and polishing processes; the moisture content of the core wood panel is 5-8%, and the moisture content of the eucalyptus core panel is 6-12%. The balancing layer is a bleached poplar veneer or a high-density fiberboard without added formaldehyde; The hardened base coating has a smoothness of Ra0.3-0.5 after sanding, and a surface hardness of 3-5H.
3. A method for preparing a formaldehyde-free decorative panel according to any one of claims 1 or 2, characterized in that: The specific process includes: S1 Formaldehyde-free adhesive preparation; S2 Formaldehyde-free plywood and formaldehyde-free blockboard substrate preparation; S3 formaldehyde-free plywood and formaldehyde-free blockboard substrate production; S4 formaldehyde-free substrate hardened; S5 high surface performance formaldehyde-free paper preparation; S6 formaldehyde-free decorative panel composite production.
4. The method for preparing the formaldehyde-free decorative panel according to claim 3, characterized in that: The formaldehyde-free adhesive is a modified acrylic resin adhesive. The preparation of the formaldehyde-free adhesive is the preparation of the modified acrylic resin. The specific steps include: S11 prepare raw materials: 20-25 parts of acrylic acid monomer, 50-60 parts of acrylate monomer, 10-16 parts of hydroxyl functional body, 5-10 parts of polyvinyl alcohol, 2-4 parts of emulsifier, 0.02-0.06 parts of initiator, 60-90 parts of deionized water; The acrylic acid monomer is one or a mixture of two of acrylic acid, methyl acrylate or ethyl acrylate; The acrylic acid ester monomer is obtained by methyl acrylate and isoprene glycol through an ester exchange reaction; Preparation of S12 modified acrylic resin emulsion: First, acrylic acid monomer, acrylic ester monomer and deionized water are mixed, and then hydroxyl functional body, polyvinyl alcohol, emulsifier and initiator are added, and the mixture is reacted for 2-6 hours at 40-80° C. and 300-800 rpm under nitrogen protection to obtain a modified acrylic resin emulsion; Preparation of S13 formaldehyde-free adhesive: The prepared modified acrylic resin emulsion is used as the main body, a part of flour is added as filler, and a certain amount of humidity-adjusting materials such as calcium chloride or magnesium chloride are added. The mixture is stirred at a high speed of 500-3000 revolutions per minute for 10-15 minutes to obtain the modified acrylic resin glue, which is the formaldehyde-free adhesive; the modified acrylic resin emulsion: flour: humidity-adjusting material = 80-100:20-25:0.5-1.
5. The method for preparing the formaldehyde-free decorative panel according to claim 3, characterized in that: The preparation of the formaldehyde-free plywood and formaldehyde-free blockboard substrate comprises the following specific steps: S21 prepare materials: formaldehyde-free adhesive and core material; The core material is one or both of a formaldehyde-free blockboard core and a eucalyptus core board; the moisture content of the blockboard core is 5-8%, and the moisture content of the eucalyptus core board is 6-12%; S22 Gluing and Assembly: The core materials are assembled in a crisscross pattern according to the design plan. The amount of formaldehyde-free adhesive applied is 160-170g / m², and the gluing time is controlled within 40-60 minutes. S23 cold pressing: set the cold pressing time to 40-80 minutes and the pressure to 0.6-0.9MPa; S24 core repair: cut off the overlap and fill the gap between the missing core and the gap; S25 hot pressing: temperature 120-130℃, time 20-60 minutes, pressure 0.6-0.9MPa, hot pressing to the moisture content of the blank is 7-9%, moisture content deviation is 1-2%; after cold pressing, the blank is hot pressed within 12 hours; S26 fixed thickness sanding: select 60 and 120 mesh combination sanding belts, sand to the specified thickness of 15-16mm, the thickness deviation of the board is within 0.2mm, and the board surface finish is Ra1.5-1.7; S27 scraping putty: fill the missing core of the flat surface; S28 trimming: One-time trimming to obtain formaldehyde-free plywood and formaldehyde-free blockboard substrates, with a cutting amount of 20-30mm; S29 curing: the curing period is 5-8 days, and the formaldehyde-free plywood and formaldehyde-free blockboard substrate are obtained.
6. The method for preparing the formaldehyde-free decorative panel according to claim 3, characterized in that: The production of the formaldehyde-free plywood and formaldehyde-free blockboard substrate comprises the following specific steps: S31 Prepare materials: formaldehyde-free adhesive; formaldehyde-free plywood and formaldehyde-free blockboard substrate; poplar bleached veneer or high-density fiberboard balance layer; The water content of the poplar bleached veneer is 8-12%, and the density of the high-density fiberboard is 800-950kg / m³; S32 Glue coating: A bleached poplar veneer or high-density fiberboard balancing layer is laminated on the top and bottom of the formaldehyde-free plywood and formaldehyde-free blockboard substrates, and the amount of formaldehyde-free adhesive coating is 140-150g / m 2 , the gluing time is controlled within 20-40 minutes; S33 cold pressing: within 40-70 minutes, pressure 0.7-0.75MPa; S34 hot pressing: set the hot pressing temperature to 115-125℃, the time to 5-10 minutes, the pressure to 0.6-0.9MPa, and control the moisture content after hot pressing to 7-8%; S35 sanding: Use 240-250 mesh sanding belt to polish, sand until the thickness deviation of the board is within 0.15mm, the board surface is flat, and the finish is Ra0.7-0.9; S36 trimming: Second trimming to obtain formaldehyde-free plywood and formaldehyde-free blockboard substrate; S37 curing: setting the number of days to 8-12 days, to obtain the formaldehyde-free plywood and formaldehyde-free blockboard substrate.
7. The method for preparing the formaldehyde-free decorative panel according to claim 3, characterized in that: The formaldehyde-free substrate hardening treatment specifically comprises the following steps: S41 material preparation: The modified hard primer is a saturated polyester resin coating modified with silicone, which is compounded with acrylic paint, silicone, shielding agent and curing agent. The proportion of each component is: acrylic paint: silicone: shielding agent: curing agent = 100: 1-2: 3-6: 0.2-0.5; its main components are dimethyl diethyl silane, ethylene glycol, terephthalic acid, ion exchanger, silicone, magnesium silicate and polyisocyanate; S42 coating treatment: coating operation is carried out after curing of the formaldehyde-free substrate. The coating amount for the first coating is 30-40g / m²; S43 polishing: polishing with 240 mesh and 320 mesh combination abrasive belts to ensure a smooth and clean surface with a finish within Ra0.4-0.6 and a surface hardness of 2-4H; S44 curing and curing: the curing and curing time is set to 3-5 days; S45 coating treatment: After the substrate is first coated, polished, cured and solidified, a second coating is carried out, with a coating amount of 30-40g / m²; S46 polishing: polish the surface again, using a combination of 240-mesh and 320-mesh abrasive belts to further improve the surface quality, with a finish Ra of 0.4-0.5 and a surface hardness of 3-4H; S47 curing: set the number of days to 5-10 days to obtain hardened formaldehyde-free plywood and formaldehyde-free blockboard substrates.
8. The method for preparing the formaldehyde-free decorative panel according to claim 3, characterized in that: The preparation of the formaldehyde-free paper with high surface performance comprises the following specific steps: S51 prepare raw materials: 76-82 parts of acrylic emulsion, 15-20 parts of melamine resin, 0.3-0.4 parts of catalyst p-toluenesulfonic acid, 0.12-0.18 parts of wetting agent, 0.1-0.13 parts of penetrant, 0.1-0.2 parts of defoamer, 3-8.2 parts of deionized water, pre-impregnated paper, and apply water-based paint; The tensile strength of the pre-impregnated paper is 40N / 10m-60N / 20m, and the gram weight is 50-80g / m²; The water-based coating is water-based acrylic emulsion, water-based polyurethane or polyacrylate; Preparation of S52 water-based amino resin: S521 weigh a certain amount of melamine resin according to the ratio, add deionized water, and dilute the melamine resin to a mass fraction of 50-60%; S522 Add the diluted melamine resin into the quantitative acrylic emulsion, stir at 800-1200 rpm for 4-5 minutes, and then reduce the speed; S523 then add catalyst, wetting agent, penetrant, defoamer and other corresponding additives, stir evenly to obtain water-based amino resin for standby use; S53 roller coating process: S531 is roller coated using a specific coating roller, and the prepared water-based amino resin is injected between the coating rollers; The S532 pre-impregnated paper is horizontally unwound by an unwinder, and then coated with a water-based coating on the surface by a roller coater to obtain a surface coating; S533 is dried in a dryer to control the tensile strength of the pre-impregnated paper to be 40N / 10m-60N / 20m and the gram weight to be 50-80g / m², thereby obtaining formaldehyde-free facing paper with certain decorative properties and surface properties, namely the formaldehyde-free paper with high surface properties.
9. The method for preparing the formaldehyde-free decorative panel according to claim 3, characterized in that: The composite production of the formaldehyde-free decorative panel specifically comprises the following steps: S61 Dust Removal: The substrate is subjected to three dust removal processes: electrostatic, brush and air blowing; S62 glue coating and lamination: The glue coating uses polyvinyl acetate or polyurethane formaldehyde-free fast curing adhesive, and the glue coating amount is 30-40g / m 2 , the board feeding speed is 10-20 meters per minute, the tension of the formaldehyde-free paper support roller is 9-12N / m, and the paper tension modulation is 10-20N / 10-20mm; S63 Roller Pressing: Set the roller pressing pressure to 0.7-0.9 mm and the time to 2-10 minutes; S64 trimming: trims excess paper edges to ensure consistent size; S65 curing and curing: set the curing and curing time to 24-48 hours to obtain the new formaldehyde-free decorative panel.
Citation Information
Patent Citations
Thin blockboard and manufacturing method thereof
CN103213178A
Formaldehyde-free consolidated composite floor and fabrication technology thereof
CN104746845A
High-weather-resisting type green recombined decorative veneer and preparation method thereof
CN108045037A
Impregnated film paper veneer blockboard free from formaldehyde release as well as production process thereof
CN110341009A
Low-formaldehyde impregnated film adhesive paper veneer artificial board and preparation method thereof
CN111421623A